UV Filtering of Dye-Sensitized Solar Cells: The Effects of Varying the UV Cut-Off upon Cell Performance and Incident Photon-to-Electron Conversion Efficiency - Matthew Carnie; Trystan Watson; David Worsley (International Journal of Photoenergy)
With current technology, UV filters are essential to ensure long-term dye-sensitized solar cell (DSC) stability. Blocking photons, however, will have an obvious effect on device performance and upon its incident photon-to-current conversion efficiency (IPCE). Filters have been applied to DSC devices with a range of cut-off wavelengths in order to assess how different levels of filtering affect the performance and IPCE of devices made with three different dyes, namely N719, Z907, and N749. It is shown that dyes that extend their IPCE further into the NIR region suffer lesser relative efficiency losses due to UV filtering than dyes with narrower action spectra. Furthermore, the results are encouraging to those working towards the industrialisation of DSC technology. From the results presented it can be estimated that filtering at a level intended to prevent direct band gap excitation of the TiO2 semiconductor should cause a relative drop in cell efficiency of no more than 10% in forward illuminated devices and no more than 2% in reverse illuminated devices.